Efficacy of Cytomegalovirus Specific Immunoglobulins to Reduce CMV Reactivation in Pediatric Hematopoietic Stem Cell Transplant Recipients. Issue 1 (22nd January 2023) - Geurten, Claire; Ghinai, Rosanna; Munford, Haydn; Lawson, Sarah
Abstract : Cytomegalovirus (CMV) infection is a serious complication of pediatric hematopoietic stem cell transplant (HSCT). To date, antiviral therapy has been the mainstay of prophylaxis, with conflicting results regarding the benefits of CMV-specific immunoglobulins (CMV-Ig). After introducing prophylactic CMV-Ig to HSCT recipients at risk (seropositive recipient and/or donor), we conducted a single-center retrospective study comparing the incidence and severity of CMV infection with and without CMV-Ig. We identified 49 'at risk' recipients from 76 consecutive HSCTs over 3.5 years, in addition to standard antiviral prophylaxis, 10 patients received CMV-Ig and 39 did not. There was no significant difference in donor type, cell source, conditioning, or CMV status between the groups. We observed a potential trend toward reduction of incidence of CMV reactivation in patients exposed to CMV-Ig (30%) compared with those who weren't (38.4%). Besides, no symptomatic or lethal infection was observed in the CMV-Ig group, and time to recovery seemed shorter (21 [±7] vs 51.4 [±55] days) and peak titers lower (4578 [±4788] vs 24131 [±49257]) with CMV-Ig. No adverse events were noted. The statistical significance of the results was limited by the small sample size. These data raise interest in prophylactic CMV-Ig as a safe way of potentially reducing the severity and duration of CMV reactivation in HSCT.